Stormwater Ponds in the Southeastern U.S. Coastal Plain: Hydrogeology, Contaminant Fate, and the Need for a Social-Ecological Framework - Beckingham, Barbara; Callahan, Timothy; Vulava, Vijay (Frontiers in Environmental Science, 2019)
In lowland coastal regions of the southeastern United States, stormwater ponds are being built as the “green infrastructure” best management practice of choice for addressing the hydrologic changes associated with rapid urban and suburban development. In addition to dampening storm flows, stormwater ponds may provide pollution control and other ecosystem services. However, ponds are not native to this landscape. This review summarizes what is known about the effectiveness of these engineered ponds, which take many shapes and forms, in the context of hydrology, contaminant fate, and management. Research needs are identified and include evaluating pond performance and redesign options more comprehensively and applying a social-ecological framework for the future of stormwater pond management.